Assessment of the state of free radical oxidation in patients with lichen plus by the chemiluminescence method - M. N. Vildanov; L. P. Gerasimova; T. S. Chemikosova; A. A. Golub (Эндодонтия Today)
One of the non-invasive methods for assessing oxidative stress is the study of the oral fluid of patients by chemiluminescence. Based on the data obtained, it is possible to quantify the degree of oxidative stress and adjust the prescribed therapy.Objectives. To assess the state of free radical oxidation of the oral fluid by chemiluminescence (CL) in patients with various verified forms of oral lichen planus (OLP), compare the data obtained with those in the control group.Materials and methods. 287 patients with various forms of OLP of the oral mucosa and 32 patients of the control group, comparable in sex and age, were studied. The assessment of oxidative stress was carried out using the device HL-003, examining the oral fluid.Results. The parameters S, Imax of individual forms of OLP had statistically significant differences compared with those of the control group of patients. Thus, the erosive-ulcerative form of OLP by the S parameter exceeded the conditional norm by 2.45 times, by the Imax parameter it exceeded by 2.37 times; exudative-hyperemic form exceeded the norm in parameter S, exceeded the conditional norm by 2.12 times, in parameter Imax exceeded 1.71 times; atypical form of OLP had a statistically significant excess in Imax by 1.49 times; the bullous form of OLP had a statistically significant excess in the S parameter by 2.18 times. Other forms of OLP (typical, hyperkeratotic) did not have statistically sign100ificant differences in the parameters S, Imax.Conclusions. The obtained data substantiate the inclusion of antioxidant therapy in the ongoing OLP therapy; indicators of CL in the oral fluid can be one of the biomarkers in the diagnosis and monitoring of therapy in OLP, especially in the long term, mainly in erosive-ulcerative, exudative-hyperemic, atypical and bullous forms of OLP.